Community Participation in Infrastructure Maintenance in North Aceh Regency - Syahputra, Randa; Rahman, Dahlan A.; Fazil, Muhammad; M. Akmal (Jurnal Transparansi Publik (JTP), 2025)
Community participation is the most important thing in infrastructure maintenance. Without community participation, the development built by the government will not last long if it is not properly cared for by the community. Community participation in infrastructure maintenance in Aceh Utara using the theory according to Cohen and Uphoff cited by Joyce and Joorie (2021) namely Participation in Decision Making, Participation in Implementation, Participation in Utilization, and Participation in Evaluation. The type of research used is qualitative descriptive with data collection techniques in the form of interviews, documentation and observations. The sampling technique was carried out by purposive sampling. The data source uses primary data, secondary data. Data analysis techniques with data reduction, data presentation, and conclusion drawn. The results of the study show that community participation in infrastructure maintenance in Aceh Utara is still not optimal, which can be seen from Participation in Decision Making is still relatively low. Participation in Implementation There is still a low level of awareness and community involvement. Participation in Utilization There is still a low awareness in maintaining, caring for and maintaining every development result made by the government and Participation in Evaluation often criticizes the government, but the government does not respond to criticism from the community. The factors that cause the lack of community participation in infrastructure maintenance in Aceh Utara are economic factors that make people reluctant to participate and from environmental factors that lack a sense of concern in infrastructure maintenance. It is recommended to the Public Works and Spatial Determination Office of North Aceh Regency to further increase public awareness and concern in carrying out infrastructure maintenance, such as providing socialization and guidance for the gampong community regarding the importance of infrastructure maintenance.